Dr. Novel and Dr. Sage: Developing Expertise in Leading Small-Group Discussions - Laurie Fishman; Lori Newman (MedEdPORTAL, 2014)
Abstract Introduction As medical schools increasingly move toward student-centered, interactive learning approaches that promote active student engagement and critical thinking skills, there is a clear trend to employ teaching methods that emphasize collaborative, case-based instruction. Small-group teaching offer students the opportunity to build upon their existing knowledge by becoming active participants in the examination of a clinical topic or patient case. To be skilled at small group facilitation involves planning and design, managing learning during the discussion, and feedback and reflection after each session. Faculty training is essential for developing the skills necessary to be an effective small-group facilitator. Methods The teaching case and accompanying facilitator's guide included in this module provide a comprehensive set of skills and resources that can be readily used by those charged with leading a faculty development session about small-group facilitation. Participants of such a faculty development session work through the problem-based teaching case, and, by addressing common small-group discussion dilemmas, learn the skills needed to facilitate an effective discussion. The resources are intended to be used during a stand-alone, live, interactive training session. The case is structured using a problem-based learning format so that participants can experience small-group teaching in the role of the learner. The intended audience for the faculty development session is junior faculty or novice facilitators as well as senior faculty or facilitators, who will more than likely value the opportunity to share their own experiences in leading small-group discussions. Results This small-group teaching session and case has been presented 13 times at Boston Children's Hospital, as part of faculty development efforts at Harvard Medical School, at a national subspecialty conference, and at the national Harvard Medical School CME Course “Principles of Medical Education.” Group size has ranged from four to 40 and participants have included residents, fellows, physicians, and health care professionals from a wide variety of specialties. Discussion Through the experience of presenting this session on multiple occasions, we have learned that it is best to start by asking the audience members to assume the role of participant-observers; in other words, to participate in the exercise, but at the same time take a mental step back and observe the teaching strategies the facilitator models during the session. It is also helpful to mention that the facilitator will be modeling, and then stopping to point out, certain teaching behaviors, strategies, and nonverbal gestures/cues throughout the session.